The Edinburgh companion to modern Jewish fiction - Brauner, David, 1968-; Stähler, Axel (Edinburgh companions to literature, 2015)
"WINNER of the Association of Jewish Libraries' Judaica Reference Award. Provides critical overviews of the main writers and key themes of Anglophone Jewish fiction. This collection of essays represents a new departure for, and a potentially (re)defining moment in, literary Jewish Studies. It is the first volume to bring together 28 chapters covering a wide range of American, British, South African, Canadian and Australian Jewish fiction. The volume is divided into 3 parts - American Jewish Fiction; British Jewish Fiction; and International and Transnational Anglophone Jewish Fiction - but many of the essays cross over these boundaries and speak to each other implicitly, as well as, on occasion, explicitly. Extending and redefining the canon of modern Jewish fiction, the volume juxtaposes major authors with more marginal figures, revising and recuperating individual reputations, rediscovering forgotten and discovering new work, and in the process remapping the whole terrain. This volume opens windows onto vistas that previously had been obscured and opens doors for the next generation of studies that could not proceed without a wide-ranging, visionary empiricism grounding their work. Key Features. Highlights the rich diversity of the field and identifies its key themes, including immigration, the Diaspora, the Holocaust, Judaism, assimilation, antisemitism and Zionism Analyses the main trends in Anglophone Jewish fiction and situates them in historical context Discusses the place of Anglophone Jewish fiction in relation to critical debates concerning transatlanticism and transnationalism; ethnicity and identity politics; postcolonial studies, feminist studies and Jewish Studies With a preface by Mark Shechner, the volume's contributors include Vicki Aarons (Trinity University, Texas), Debra Shostak (Wooster College, Ohio), Ira Nadel (University of British Columbia), Efraim Sicher (Ben-Gurion University), Phyllis Lassner (Northwestern University), Sue Vice (University of Sheffield), Lori Harrison-Kahan (Boston College), Ruth Gilbert (University of Winchester), Beate Neumeier (University of Cologne) and Sandra Singer (University of Guelph)"--